Beyond Borders : Stories of Yunnanese Chinese Migrants of Burma - Chang, Wen-Chin, 1964-; Project Muse. (London : Cornell University Press, 2014)
The Yunnanese from southwestern China have for millennia traded throughout upland Southeast Asia. Burma in particular has served as a "back door" to Yunnan, providing a sanctuary for political refugees and economic opportunities for trade explorers. Since the Chinese Communist takeover in 1949 and subsequent political upheavals in China, an unprecedented number of Yunnanese refugees have fled to Burma. Through a personal narrative approach, Beyond Borders is the first ethnography to focus on the migration history and transnational trading experiences of contemporary Yunnanese Chinese migrants (composed of both Yunnanese Han and Muslims) who reside in Burma and those who have moved from Burma and resettled in Thailand, Taiwan, and China. Since the 1960s, Yunnanese Chinese migrants of Burma have dominated the transnational trade in opium, jade, and daily consumption goods. Wen-Chin Chang writes with deep knowledge of this trade's organization from the 1960s of mule-driven caravans to the use of modern transportation, and she reconstructs trading routes while examining embedded sociocultural meanings. These Yunnanese migrants' mobility attests to the prevalence of travel not only by the privileged but also by different kinds of people. Their narratives disclose individual life processes as well as networks of connections, modes of transportation, and differences between the experiences of men and women. Through traveling they have carried on the mobile livelihoods of their predecessors, expanding overland trade beyond its historical borderlands between Yunnan and upland Southeast Asia to journeys further afield by land, sea, and air
Migration history -- The days in Burma: Zhang Dage -- Entangled love: Ae Maew -- Pursuit of ambition: father and son -- Islamic transnationalism: Yunnanese Muslims -- (Transnational) trade -- Venturing into barbarous regions: Yunnanese caravan traders -- Transcending gendered geographies: Yunnanese women traders -- Circulations of the jade trade: the Duans and the Pengs -- Epilogue: from mules to vehicles.
In English.
Description based on print version record.
Keywords: Muslims; Emigration and immigration; Chinese -- Migrations; Chinese; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Minority Studies; SOCIAL SCIENCE -- Discrimination & Race Relations; Society and social sciences Society and social sciences; Society and culture : general; Social issues and processes; Migration, immigration and emigration; Musulmans -- Birmanie; Chinois -- Birmanie; Muslims -- Burma; Chinese -- Burma; Chinese -- Migrations; Thailand; China; Burma; Thailand -- Emigration and immigration; China -- Emigration and immigration; Burma -- Emigration and immigration; Electronic books